The existence of C(4)-bundle-sheath-like photosynthesis in the mid-vein of C(3) rice - Shen, Weijun (Rice (N Y), 2016)
BACKGROUND: Recent studies have shown that C(4)-like photosynthetic pathways partly reside in photosynthetic cells surrounding the vascular system of C(3) dicots. However, it is still unclear whether this is the case in C(3) monocots, especially at the molecular level. RESULTS: In order to fill this gap, we investigated several characteristics required for C(4) photosynthesis, including C(4) pathway enzymes, cyclic/non-cyclic photophosphorylation rates, the levels and assembly state of photosynthetic machineries, in the mid-veins of C(3) monocots rice with leaf laminae used as controls. The signature of photosystem photochemistry was also recorded via non-invasive chlorophyll a fluorescence and reflectance changes at 820 nm in vivo. Our results showed that rice mid-veins were photosynthetically active with higher levels of three C(4) decarboxylases. Meanwhile, the linear electron transport chain was blocked in mid-veins due to the selective loss of dysfunctional photosystem II subunits. However, photosystem I was sufficient to support cyclic electron flow in mid-veins, reminiscent of the bundle sheath in C(4) plants. CONCLUSIONS: The photosynthetic attributes required for C(4) photosynthesis were identified for the first time in the monocotyledon model crop rice, suggesting that this is likely a general innate characteristic of C(3) plants which might be preconditioned for the C(4) pathway evolution. Understanding these attributes would provide a base for improved strategies for engineering C(4) photosynthetic pathways into rice. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12284-016-0094-5) contains supplementary material, which is available to authorized users.